2007
DOI: 10.1177/1076029607310217
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilia in Human Immunodeficiency Virus—Infected Patients with Osteonecrosis: Is There a Real Connection? The First Case-Control Study

Abstract: Several reports have described an increased incidence of osteonecrosis in human immunodeficiency virus-infected patients (HIV+), but the cause has not been established. The association between thrombophilia and osteonecrosis in HIV+ was studied. A case-control study in HIV+, 19 cases and 38 controls, was designed. Magnetic resonance imaging was made in both groups to confirm or exclude hip osteonecrosis. The extensive tests of thrombophilia were measured, and the clinical data were recorded, nadir of CD4(+) ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…4,6,9,11 Our data for steroid exposure are broadly comparable to that of Fessel et al, 13 in terms of aggregate corticosteroid dose given per month prior to AVN diagnosis and the dose given in the year prior to AVN diagnosis. In addition, the proportion who had received corticosteroids in the year prior to AVN diagnosis was 5/15 (33%) in our data compared with (3/12) 25% for Fessel et al Suggestions of how steroid exposure mediates cell death include increased apoptosis through activation of free radicals and inflammatory mediators, 4 increased intraosseous pressure due to fat infiltration of bone marrow causing obstruction in small blood vessels 11 or fat embolization in vessels through secondary hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…4,6,9,11 Our data for steroid exposure are broadly comparable to that of Fessel et al, 13 in terms of aggregate corticosteroid dose given per month prior to AVN diagnosis and the dose given in the year prior to AVN diagnosis. In addition, the proportion who had received corticosteroids in the year prior to AVN diagnosis was 5/15 (33%) in our data compared with (3/12) 25% for Fessel et al Suggestions of how steroid exposure mediates cell death include increased apoptosis through activation of free radicals and inflammatory mediators, 4 increased intraosseous pressure due to fat infiltration of bone marrow causing obstruction in small blood vessels 11 or fat embolization in vessels through secondary hyperlipidaemia.…”
Section: Discussionsupporting
confidence: 79%
“…Established risk factors for AVN in individuals without HIV (such as alcohol abuse, corticosteroid use, coagulopathies) may be more prevalent in those with HIV. [4][5][6][7][8][9][10][11] Moreover, it has been suggested that HIV infection itself and antiretroviral therapy (ART), particularly protease inhibitors (PIs), 12 may increase AVN risk. This study investigates the association of AVN in HIV-positive individuals with possible risk factors including ART.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, many reports have documented an increased risk of venous and arterial thrombosis in HIVinfected patients [10][11][12]. Our observations during clinical practice indicate that female patients with HIV infection are more prone to venous and arterial thrombosis than male patients.…”
Section: Introductionsupporting
confidence: 57%
“…In the past few years, an increased risk of venous and arterial thrombosis in HIV-infected patients has been documented [10][11][12]. This is partly correlated with an increased serum level of antiphospholipid and anticardiolipin antibodies in these patients [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%